PENGETAHUAN BIDAN TENTANG MANAJEMEN LAKTASI MASA PANDEMI COVID-19 DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS GLUGUR DARAT - Elvina Sari Sinaga; Rika Fransiska; Revina Lusiana Sitorus; Sri Diana (Jurnal Ilmiah Kebidanan Imelda, 2022)
Based on the health of profil North Sumatra Utara (2019), the district/cities with the highest coverage of exclusive brrestfeeding are north Nias (84,28%), Sibolga (72,12%), and Samosir (69,5%). While ther 3 lowest regencies/cities arer west, Serdang Bedagai (16,20%), Nias (11,96%), an Nias (17,62%). Its is feared that location during the Covid-19 pandemic has decreased, due to the lack of knowledge of midwives. So it is necessary to study related to the knowledge of midwives about lacation management during the Covid-19 pandemic in the working area of the Glugur Darat Center. The type of this research is correlation analytic research with cross sectional design. The population in this study were all midwives who were in the working area of the Glugur Darat Health Center, the entire population was sampled as many as 30 people. Primary data collection using a questionnaire made by the researcher himself. Data analysis was carried out by using the Chi Square test using SPSS with a significant llevel of < 0,05. In conclusion, there is a relationship between midwives’ knowledge of locatin management during of Covid-19 pandemic and ecxclusive brestfeeding in the working area of the Glugur Darat Health Center.